NET PROFIT MARGIN, CAPITAL STRUCTURE AND ECONOMIC VALUE ADDED AS PREDICTORS OF STOCK RETURNS IN BASIC MATERIALS - Herwanto, Paramuditha Citra Mutiara; Fauzi, Achmad; Indriani, Susi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
Stocks are a type of investment with the highest level of risk compared to other investment instruments. Factors that can influence investment risk include market risk, price fluctuations, company management, company performance, and financial performance. This study aims to analyze net profit margin (NPM), capital structure, and economic value added (EVA) on stock returns. The method used in this study is quantitative, with data collected from annual financial reports. The study population consisted of 93 companies in the basic materials sector. The research sample was determined using a simple random sampling technique and calculated using the Slovin formula with a 5% error rate, to obtain a sample of 75 companies with an observation period of 2022-2023, resulting in 150 observation data. The results show that simultaneously the variables NPM, Capital Structure, and EVA do not significantly affect stock returns, but partially NPM has a significant effect on stock returns. Capital structure, proxied by the Debt to Equity Ratio (DER), does not significantly affect stock returns. EVA does not significantly affect stock returns. Practically, this research can be a basis for companies as a consideration in improving company performance and company value and investors are expected to gain knowledge before making investment decisions.